KONSEP PERNIKAHAN MASYARAKAT SAMIN DAN PENDEKATAN DAKWAH KULTURAL - Damsuki, Ali (Islamic Communication Journal, 2019)
The human patterns and behavior in the dynamics of society have internal uniqueness in forming a habit. The pattern and behavior become a social construction that tends to humanist values so that it has implications for culture. Culture is the result of human creativity, initiative, and taste. Culture represents a distinctive feature for people living in an area. The Samin community remains a group that adheres to the teachings of Saminism. In the Samin community, the culture of the wedding ceremony is contrary to Islam. There are so many things deviate from Islamic ways, such as the term “weton” (birthday) which is frequently used as the fundamental tendency for the Samin community in determining marriage mates, days and dates of marriage in a Javanese perspective and do not involve the KUA in the marriage procession. In Islam, marriage unlimited to the symbol of the birthday of every couple, both male and female. This is explained in al-Dzariyat: 49. After the presence of Islam as a religion of da'wah, the culture of the Samin community began to experience systematic changes, both religious and nationalist through the propagation of empowerment with a cultural approach. Empowerment of da'wah with a cultural approach gradually began to come into contact with the culture of the Samin community which tended to be "conservative." This change occurred through the acculturation of Samin's Islamic marriage culture and administrative records by KUA. These changes occur through the acculturation of the culture of Samin's Islamic marriage and administrative records by the KUA.